1987
DOI: 10.1677/joe.0.1120443
|View full text |Cite
|
Sign up to set email alerts
|

Influence of administration of ovarian steroids on the function of neutrophils isolated from the blood and uterus of ovariectomized mares

Abstract: The function of blood and uterine luminal neutrophils from ovariectomized mares treated with ovarian steroids was investigated 18 h after intrauterine infusion of 1 X 10(9) Streptococcus zooepidemicus. Random migration of blood neutrophils under agarose was reduced by treatment with progesterone compared with that of neutrophils from oestradiol-treated and control mares. In-vitro addition of progesterone to blood neutrophils from acyclic ponies also reduced migration. Uterine neutrophils did not migrate under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 12 publications
0
8
1
Order By: Relevance
“…The discrepancy between those reports and the present study may be explained in part by the well-documented influence of the estrous cycle on PMN functions [23][24][25]. Consequently, it is probably inappropriate to compare experiments from different stages of the estrous cycle.…”
Section: Discussioncontrasting
confidence: 84%
“…The discrepancy between those reports and the present study may be explained in part by the well-documented influence of the estrous cycle on PMN functions [23][24][25]. Consequently, it is probably inappropriate to compare experiments from different stages of the estrous cycle.…”
Section: Discussioncontrasting
confidence: 84%
“…HENRICKS et al (1987) reported that the metabolic responsiveness of neutrophils is diminished and the accumulation of phagocytic cells at the site of infection is reduced after a stress period. Although studies have been reported on the effect of corticoids on leukocyte migration ( ROTH et al, 1983;WATSON et al, 1987), the results have been contradictory. Further studies are necessary to determine the exact mechanism of the effects of corticosteroids on neutrophil function.…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone treatment makes previously resistant mares susceptible to bacterial challenge (Evans et al 1986, Reilas et al 1998). Although there is evidence for the adverse effects of progesterone and beneficial effects of oestrogen on PMN functions , Watson et al 1987c, the effects on the physical drainage of the uterus are much more obvious. Under the influence of progesterone the cervix is closed, whereas under oestrogen dominance it stays open.…”
Section: Effects Of Ovarian Steroidsmentioning
confidence: 99%
“…They have been exposed to bacterial stimulation, they have responded to chemotactic stimuli, migrated and phagocytised, which changes their ability to deform. This may have changed their ability to migrate and kill bacteria (Watson et al 1987c). Many of the proposed dysfunctions for PMNs from the uterus of susceptible mares can be related to the adverse uterine luminal environment (Liu et al 1986).…”
Section: Polymorphonuclear Leukocytes (Pmn)mentioning
confidence: 99%